Old and New-Old Theories of Income Distribution - Tonveronachi, M. (Journal of Income Distribution®, 1994)
The purpose of the paper is to recall the main features of Keynes's theory of income distribution in order to evaluate those recent contributions that go under the label of new Keynesian theory. To this end, a succinct overview of some leading pre-Keynesian theories and of Keynes approach in his Treatise on Money is first offered. After that, some exercises with the set of hypotheses on which the Treatise is based and a discussion of the General Theory clarify the theoretical operation proposed by Keynes. It is finally argued that the new Keynesian contributions are both analytically faulty and not coherent with Keynes’s vision of the working of the capitalist system.